<span> equilateral triangle is a triangle in which all three sides are equal. In traditional or Euclidean geometry equilateral <span>triangle
</span></span>
Answer: 0.9844
Step-by-step explanation:
given data:
sample size n = 6
It’s assumed that half the population are male and the remaining half are females
F = 1/2
M = 1/2
the probability that the investigator would draw altleats one male
P ( x ≥ 1 ) =
= 1 - ( 0.5 ) ^ 6
= ( 0.5 )^6
= 0.9844
Answer:
x = 2.2
Step-by-step explanation:
Comment
f(x) = g(x) I don't think has any meaning for this question. I will just solve the equation.
Solution
7x - 12 = - 3x + 10 Add 3x to both sides
7x + 3x -12 = - 3x + 3x +10 Combine
10x - 12 = 10 Add 12 to both sides
10x -12 + 12 = 10 + 12 Combine
10x = 22 Divide by 10
10x/10 = 22/10
x = 2.2
Answer: 80 pieces of fruit
Explanation:
Let’s find out the amount of trees Mr Champion has.
He has 14 in total. 1 apple tree and 1 plum tree, and the rest are divided evenly among apricot, pear and peach trees. This means:
1 apple tree + 1 plum tree = 2 trees
14 - 2 = 12 trees
12 / 3 (varieties of trees) = 4
In conclusion, he has
1 apple tree, 1 plum tree, 4 apricot, pear and peach trees.
Now let’s go to the section where he picks the fruit.
6 apricots from 4 trees
10 peaches from 4 trees
3 pears from 4 trees
4 apples from 1 tree
This means:
(6 x 4) + (10 x 4) + (3 x 4) + (4 x 1) = total pieces of fruit picked
24 + 40 + 12 + 4 = total pieces of fruit picked
Now, you add up those four numbers, and you have your answer, 80.
Hope this helps!
The product of something means multiplying the terms together.
(2x+3) (4x^2-5x+6)
Secondly you need to distribute the terms to each other (Think of problems like FOIL)
2x * 4x^2 + 2x(-5x) + 2x * 6 + 3 * 4x^2 + 3(-5x) + 3 * 6
Then you must take into account that some of the numbers are negative. (minus-plus rules!)
2x * 4x^2 - 2x * 5x + 2x * 6 + 3 * 4x^2 - 3 * 5x + 3 * 6
Now is the tricky part of simplifying everything.
2x * 4x^2 = 8x^3
2x * 5x = 10x^2
2x * 6 = 12x
3 * 4x^2 = 12x^2
3 * 5x = 15x
3 * 6 = 18
8x^3 - 10x^2 + 12x + 12x^2 - 15x + 18
Then you group like terms.
8x^3 - 10x^2 + 12x^2 - 3x + 18
8x^2 + 2x^2 - 3x + 18
The trickiest part of this is distributing all of the terms within the parentheses, once you've done that, it's smooth sailing!